Successful Application of a Galanin-Coated Scaffold for Periodontal Regeneration. (September 2021) - Ma, W.; Lyu, H.; Pandya, M.; Gopinathan, G.; Luan, X.; Diekwisch, T.G.H.
The nervous system exerts finely tuned control over all aspects of the life of an organism, including pain, sensation, growth, and development. Recent developments in tissue regeneration research have increasingly turned to small molecule peptides to tailor and augment the biological response following tissue loss or injury. In the present study, we have introduced the small molecule peptide galanin (GAL) as a novel scaffold-coating agent for the healing and regeneration of craniofacial tissues. Using immunohistochemistry, we detected GAL and GAL receptors in healthy periodontal tissues and in the proximity of blood vessels, while exposure to our periodontal disease regimen resulted in a downregulation of GAL. In a 3-dimensional bioreactor culture, GAL coating of collagen scaffolds promoted cell proliferation and matrix synthesis. Following subcutaneous implantation, GAL-coated scaffolds were associated with mineralized bone-like tissue deposits, which reacted positively for alizarin red and von Kossa, and demonstrated increased expression and protein levels of RUNX2, OCN, OSX, and iBSP. In contrast, the GAL receptor antagonist galantide blocked the effect of GAL on Runx2 expression and inhibited mineralization in our subcutaneous implantation model. Moreover, GAL coating promoted periodontal regeneration and a rescue of the periodontal defect generated in our periodontitis model mice. Together, these data demonstrate the efficacy of the neuropeptide GAL as a coating material for tissue regeneration. They are also suggestive of a novel role for neurogenic signaling pathways in craniofacial and periodontal regeneration.